The effect of selected resistance training on swimming records in female students - Shabkhiz, F.; Amirshaghaghi, F.; Aminian Razavi, T.; Ghelichipour, N.; Homayoun, Z. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The purpose of present study was to determine the effect of an eight-week of selected resistance training protocol on 25-50-75 and 100 meters swimming records in female physical education students. Method: 18 people of 42 female physical education students of P.E. coaching (21±1.1 years old, 164.15±2.5 cm length and 56±8.6 kg weight) selected randomly and divided to Experimental (the swimming training program + selected resistance training) and Control (the swimming training program) groups. The selected resistance training (6session/week) included muscle adaptations, strength, and power with 85% intensity of 1RM. After 8 weeks (2session/week) of swimming training, Mean± standard deviation, K-S test (to examine the normality of the groups) and Dependent and independent t-test (to determine the differences between the two groups) were used for data analyzing (á= 0.05). Results: The results indicated that the selected resistance training increased power in Scott in the leg, hand flexion), opposite stretch of hand, flexion and extension of femur motions significantly. No significant changes were seen in swimming performance between two groups [25 m (P=0/42), 50 m (P=0/30), 75 m (P=0/31) and 100 m (P=0/32) after 8-week of selected resistance training protocol but the results showed significant reduction in 25 m[E:( P=0/03) &C: (P=0/08)], 50 m [E :( P=0/003)], 75 m [E :( P=0/008) &C :( P=0/008)] and 100 m [E :( P=0/03) &C: (P=0/003)] and no significant decrease in 50 m (P=0/98) on control group swimming records after 8 weeks swimming training in both experimental and control groups. Conclusion: Generally based on the results of this study it can be concluded that the most effect of the strength training was the last 25 meters of 100m speed swimming than other quartiles. This Distance in the most competition plays a decisive role in the fate of swimmers championship medals.